2015
DOI: 10.1007/s10554-015-0745-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of myocardial infarction size with three-dimensional speckle tracking echocardiography: a comparison with single photon emission computed tomography

Abstract: To assess whether global and regional myocardial strains from three-dimensional speckle tracking echocardiography (3D-STE) correlate with myocardial infarction size (MIS) detected by single photon emission computed tomography (SPECT). Fifty-seven patients with a history of ST-segment elevation myocardial infarction (MI) within 3-6 months were enrolled, alongside 24 healthy volunteers. Left ventricular (LV) global area strain, global longitudinal strain (GLS), global radial strain, global circumferential strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…[13,14] The potential superiority of 3D-STE over 2D-STE imaging has recently been verified using cardiac magnetic resonance as a reference, in which 3D strain parameters provided higher diagnostic accuracy in reflecting the dysfunctional myocardium in an AMI animal model. [15] Cardiac dysfunction is related to myocardial fiber injury in certain directions; meanwhile, the evaluation of cardiac systolic function is the mainstay of risk assessment and management of cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,14] The potential superiority of 3D-STE over 2D-STE imaging has recently been verified using cardiac magnetic resonance as a reference, in which 3D strain parameters provided higher diagnostic accuracy in reflecting the dysfunctional myocardium in an AMI animal model. [15] Cardiac dysfunction is related to myocardial fiber injury in certain directions; meanwhile, the evaluation of cardiac systolic function is the mainstay of risk assessment and management of cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
“…GAS reflects the global function assessment of the endocardial myocardium. [22] Wang et al [14] demonstrated that 3D-GAS could gauge the value of myocardial infarction size, but its diagnostic value was not better than 3D-GLS.…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of RT3D-STE is salient for regional strain values; in particular, area, longitudinal, and circumferential 3D strains correlate with global scar extent. [30][31][32] RT3D-STE may provide indirect means for the accurate determination of transmural involvement in infarct segments. 33,34 in this context, one of the major potentials for RT3D-STE's future is the possibility to widen knowledge into cardiac pathophysiology and disease process.…”
Section: A B C Dmentioning
confidence: 99%
“…in another study, 51 impaired LV mechanics and functional capacity were found in uncontrolled and untreated hypertensive patients in comparison with controls and well-controlled hypertensives. 3D GLS, GCS, GRS, and GAS were significantly decreased in patients with untreated or inadequately Table 3 Clinical applications of real-time three-dimensional speckle tracking echocardiography Diseases Coronary artery disease Accurate assessment of Lv function and detection of early-stage Lv dysfunction, 31,37 wall motion abnormalities, 7,26,28,29 infarction size, [30][31][32][33][34] and myocardial viability 35…”
Section: Arterial Hypertensionmentioning
confidence: 99%
“…Kleijn és mtsai igazolták, hogy a 3DSTE során számított AS kvantitatív módon jellemzi a vizuális becsléssel igazolt BK-i falmozgászavarok meglétét [43]. Mindamellett az is igazolást nyert, hogy bizonyos paraméterek (például GLS) diagnosztikus erővel bírhatnak a myocardialis infarctus által érintett terület nagyságának diagnosztikájában [44]. A módszertan nagy jövővel bír, azonban további klinikai vizsgálatok szükségesek a szá-mított paraméterek diagnosztikus és prognosztikus érté-kének tisztázására.…”
Section: Strainparaméterek Számításaunclassified